A NEW APPROACH IN IMMOVABLE ASSET MANAGEMENT USING 3D SPATIAL SPACE - Uznir Ujang; Glory Annabelle Stephen; Suhaibah Azri; Nurfairunnajiha Ridzuan (International Journal of Management Studies)
Effective asset management is crucial for organizations that provide high-quality services. However, the management of immovable assets often faces challenges due to time-consuming, tedious, and error-prone paper-based practices. To address these issues, the Malaysian government has introduced MySPATA (Sistem Pengurusan Aset Tak Alih Kerajaan), an electronic-based solution aimed at improving asset management. Despite its implementation, MySPATA has not fully resolved the complications associated with locating and managing assets. This study proposes integrating three-dimensional Geographic Information Systems (3D GIS) into the asset management system to enhance productivity and accuracy. This research focuses on Taman Kobena Hall, which is managed by Majlis Bandaraya Johor Bahru (MBJB), utilizing detailed LiDAR scanning and aerial photogrammetry to create an accurate 3D model of the building. The integration of 3D GIS into the asset management system using ArcGIS software enables efficient asset registration, detailed visualization, and comprehensive data querying. The findings demonstrate that 3D visualization significantly improves asset location tracking and reduces reliance on paper-based processes, thus promoting continuous asset updates. The study also addresses the strengths and limitations of this approach. While the initial creation and maintenance of detailed 3D models require significant time and resources, the benefits of improved accuracy, better decision-making, and enhanced visualization are substantial. This research provides robust proof of the concept of integrating 3D GIS in immovable asset management and offers valuable insights for broader applications in various industries.